PENGARUH BERMAIN PROYEK DENGAN MEDIA BAHAN ALAM TERHADAP KREATIVITAS ANAK DI TK WAHYU - Elvariani, Alda; Ilyas, Sitti Nurhidayah; Parwoto, FNU (Prodi PGMI STIT Sunan Giri Bima, 2024)
The major goal of this study is to examine how Project Play affects young children's creativity. This was accomplished using a quasi-experimental design and a quantitative research methodology. A total of 30 kids were enrolled in the study, and a sample size of 24 was split into two groups: 12 were in the experimental group and 12 were in the control group. The experimental group's data analysis included descriptive statistical techniques and a non-parametric assessment of the children's creative abilities. A test statistic of -3.063 and a two-tailed p-value of 0.002—both less than the significance level of 0.05—showed a significant difference in originality between the groups. These findings imply that children exposed to Project Play activities that used natural materials as a medium demonstrated greater creativity than the control group. In conclusion, engaging in project play activities with natural materials has a significant impact on the creativity of children at Wahyu Kindergarten.